Extensive orthodontically induced dental resorption: What to do? - Alberto Consolaro
ABSTRACT If essential care is thorough, teeth with extensive orthodontically induced dental resorption can have the same endurance as normal teeth. These teeth are subjected to the same disturbances as normal ones, such as dental trauma, dental caries and periodontal disease, all of which are independent of severe dental resorption. Orthodontic retreatments of teeth presenting with extensive orthodontically induced dental resorption must take into consideration that these roots are shorter in length, therefore, they are more prone to root resorption. Conventional movements are not viable in severe resorption, but Orthodontics offer some alternatives, such as; 1) movement of multiple teeth, providing better distribution of force; 2) use of lesser forces along with bodily movements, as opposed to rotation; 3) anchorage using miniplates, which provide more diffuse and equally distributed force and movements upon teeth and bone. Extensive orthodontically induced dental resorption are not an indication for endodontic treatment. These teeth also should not be replaced by osseointegrated dental implants, but they must receive special care, as they must remain in the dental arch indefinitely.